Troubling Origins: Cyborg Politics in Larissa Lai's Salt Fish Girl - Reimer, Sharlee (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
This paper argues that Salt Fish Girl moves beyond questioning the concept of origins to suggesting that the concept itself — and the Enlightenment discourses that support racist, sexist, homophobic, and other marginalizing practices upon which the concept of origins is predicated — no longer makes sense, and that the novelist is arguing for locating connection through shared experiences.